Antioxidant and antimicrobial activities of White Radish - Mustafa Sevindik; Cavit Onat; Falah Saleh Mohammed; İmran Uysal; Oğuzhan Koçer (Turkish Journal of Agriculture: Food Science and Technology)
Since prehistoric times, humans have relied on plants for a wide variety of needs, including sustenance, shelter, thermal regulation, and medical treatment. Plants are significant organics because of the many ways they may be put to use. The white radish (Raphanus raphanistrum subsp. sativus (L.) Domin) was tested for its antioxidant and antibacterial properties, as were its tuber and aerial portions. A soxhlet was used to extract ethanol from plant material. The antioxidant and oxidant capacities were tested with the use of Rel Assay TAS and TOS kits. The agar dilution technique was used to test for antimicrobial activity against the bacteria and fungus included in the experiment. As a result of the studies, the TAS value of the tuber extract of the plant was measured as 6.698±0.187, the TOS value as 5.609±0.245 and the OSI value as 0.084±0.002. The TAS value of the herbal aerial parts extract was 4.689±0.223, the TOS value was 3.746±0.128, and the OSI value was 0.080±0.003. Inhibition of tuber extract was observed at concentrations varying between 25-100 against bacterial strains and 200 µg/mL against fungal strains. Aerial parts extract showed inhibition against bacterial strains at concentrations varying between 100-200 and against fungus strains at concentrations ranging from 200-400 µg/mL. As a result, it was determined that the white radish plant has significant antioxidant and antimicrobial activity.